Peran Teknologi Blockchain dalam Meningkatkan Transparansi dan Efisiensi Sistem Keuangan dan Akuntansi - Prawesti Ningrum, Endah; Hartono, Hartono; Adriana, Nana (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This paper examines the role of blockchain technology in enhancing transparency and efficiency within financial and accounting systems. As financial transactions become increasingly complex and globalized, the need for robust mechanisms to ensure accountability and trust has never been more critical. Through a comprehensive literature review, this study identifies key attributes of blockchain technology, including decentralization, immutability, and real-time data sharing, which contribute to improved transparency in financial reporting and auditing processes. Moreover, the analysis highlights how smart contracts can automate processes, reduce operational costs, and minimize human error, thus enhancing overall efficiency. The findings suggest that the integration of blockchain technology not only mitigates risks associated with fraud and data manipulation but also fosters greater stakeholder confidence in financial systems. Additionally, the paper discusses potential challenges and barriers to the widespread adoption of blockchain in finance and accounting, such as regulatory concerns and the need for standardization. Ultimately, this research underscores the transformative potential of blockchain technology in reshaping the financial landscape, paving the way for more transparent and efficient practices in the industry.